Altered Spontaneous Brain Activity Patterns in Children With Strabismic Amblyopia After Low-Frequency Repetitive Transcranial Magnetic Stimulation: A Resting-State Functional Magnetic Resonance Imaging Study - Wang, Yi-Ning; Pan, Yi-Cong; Shu, Hui-Ye; Zhang, Li-Juan; Li, Qiu-Yu; Ge, Qian-Min; Liang, Rong-Bin; Shao, Yi (Frontiers in Human Neuroscience, 2022)
Object: Previous studies have demonstrated altered brain activity in strabismic amblyopia (SA). In this study, low-frequency repetitive transcranial magnetic stimulation (rTMS) was applied in children with strabismic amblyopia after they had undergone strabismus surgery. The effect of rTMS was investigated by measuring the changes of brain potential using the amplitude of low-frequency fluctuation (ALFF). Material/Methods: In this study, 21 SA patients (12 males and 9 females) were recruited based on their age（7-13 years old）, weight, and sex. They all had SA in their left eyes and they received rTMS treatment one month after strabismus surgery. Their vision before and after surgery were categorized as pre-rTMS (PRT) and post-rTMS (POT). All participants received rTMS treatment, underwent magnetic resonance imaging (MRI), and their data were analyzed using the repeated measures t-test. The team used correlation analysis to explore the relationship between logMAR visual acuity and ALFF. Results: Pre- versus post-rTMS values of ALFF were significantly different within individuals. In the POT group, ALFF values were significantly decreased in the Angular_R (AR), Parietal_Inf_L (PIL), and Cingulum_Mid_R (CMR) while ALFF values were significantly increased in the Fusiform_R (FR) and Frontal_Inf_Orb_L(FIL) compared to the PRT stage. Conclusion: Our data showed that ALFF recorded from some brain regions was changed significantly after rTMS in strabismic amblyopes. The results may infer the pathological basis of SA and demonstrate that visual function may be improved using rTMS in strabismic amblyopic patients.